2021
DOI: 10.1515/phys-2021-0029
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization law of karst water in tunnel drainage system based on DBL theory

Abstract: When a tunnel is constructed in a karst area, crystallization of the drainage pipe caused by karst water often threatens the normal operation of the tunnel. This work contributes to this field of research by proposing a functional model based on the diffusion boundary layer (DBL) theory proposed by Dreybrodt in the 1990s. The model is formed by determining the flow rate distribution of the drainage pipe in a laminar flow state and turbulent state, and then by applying Fick’s diffusion law and Skelland’s approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Pipe wall roughness is a major factor influencing the crystallization rate of the tunnel drainage pipe. It is followed by the slope of the pipe wall, which can affect the water flow state by controlling the flow rate, and thus affect the crystallization rate of karst water [19,20]. In the tunnel drainage system, the most straightforward way to increase the groundwater flow rate in the drainage pipe is to increase its slope.…”
Section: Optimization Of the Materials And Slope Of Transverse Draina...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pipe wall roughness is a major factor influencing the crystallization rate of the tunnel drainage pipe. It is followed by the slope of the pipe wall, which can affect the water flow state by controlling the flow rate, and thus affect the crystallization rate of karst water [19,20]. In the tunnel drainage system, the most straightforward way to increase the groundwater flow rate in the drainage pipe is to increase its slope.…”
Section: Optimization Of the Materials And Slope Of Transverse Draina...mentioning
confidence: 99%
“…Tunnel drainage system defect is inevitable. The major research areas for domestic and foreign scholars on the tunnel drainage system range from ion sources, crystal components, and influencing factors to prevention and treatment of crystal blockage, and field survey, numerical analysis, and macro-microscopic tests are adopted as the main research methods [19,20]. The research outcomes can provide a certain reference value to the prevention and treatment of the crystal blockage of tunnel drainage systems; however, the issue cannot be thoroughly addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The partial pressure of CO 2 has a great relationship with carbonate crystallization sedimentation, and CO 3 2 − is mainly derived from CO 2 dissolved in groundwater [ 31 ]. Liquid velocity, liquid level height, drainage pipe diameter, and the internal wall friction coefficient will also have an important impact on the precipitation crystallization rate of drainage pipes [ 37 , 38 , 39 ]. The precipitation of calcium carbonate depends not only on the hydraulic conductivity and CaCO 3 content of surrounding rock, but also on the properties of lining materials and the geometry of the tunnel [ 40 ].…”
Section: Construction and Analysis Of A Fault Tree Model For Blocked ...mentioning
confidence: 99%
“…Park et al 12 analysed the relationship between pipe deterioration and blockages and found that blockages tend to cause deterioration and deterioration of the tunnel. Wang et al 13 propose a functional model based on the diffusion boundary layer (DBL) theory. The results show that the crystallisation rate of karst water is mainly influenced by the roughness of the pipe wall and, to a lesser extent, the slope of the pipe.…”
Section: Introductionmentioning
confidence: 99%